77‐2: Invited Paper: Probing the Thermal Stability of OLEDs with Neutrons. Issue 1 (May 2017) - Burn, Paul L.; McEwan, Jake A.; Clulow, Andrew. J.; Wang, Renjie; Nelson, Andrew; Gentle, Ian R.
Abstract : Organic light‐emitting diodes (OLEDs) are subjected to varying conditions of temperature during their lifetime. Using a combination of neutron reflectometry and in situ photoluminescence spectroscopy we show that layers typically found in OLEDs can interdiffuse. The diffusion is temperature dependent and it is found that the iridium(III) complexes can be remarkably mobile, even with relatively bulky alkyl groups attached to the ligand.